The Role of the Pali Regency Government in the Development of Sports Tourism to Improve the Community’s Economy - Widya Handayani; Pajar Fhatanah (Universitas Negeri Semarang, 2026)
This study analyzes the Government programs of Penukal Abab Lematang Ilir (PALI) Regency in encouraging the development of sport tourism as a response to stimulate local economy. This research aims to investigate to examine the contribution of the PALI Regency Government in promoting sport tourism, to identify the strengths and weaknesses accompanying its development process, and to propose strategic options for future sustainable development. A qualitative research approach was employed, which consisted of local government agents, event planners and community leaders. The data was collected through interviews, observation and document review and analyzed with thematic analysis approach to find the common patterns and understanding. The findings indicate that the sport tourism in PALI is relatively new and has not been deeply rooted in the regional tourism management system. Various sport and cultural events like Candi Bumi Ayu Festival have encouraged the participation of the local population and development of micro businesses. The supporting infrastructure for popular tourist sites particularly in and around Candi Bumi Ayu, is insufficient to meet the standards of visitor comfort and ease of access. In sum, the results imply that sport tourism can have considerable strategic promise in the support of local economic diversification. To continue its sustainable advancement beyond the initial enthusiasm, systemic planning, trained manpower development, infrastructure up-gradation and continued collaboration habit are necessary. These works will ensure that sporting tourism really is capable of delivering significant and sustainable economic value to our regions.